2007
DOI: 10.1007/s10658-007-9205-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and genetic diversity of Peach latent mosaic viroid and Hop stunt viroid in stone fruits in Serbia

Abstract: Tissue-imprint hybridization (TIH) assay was validated for large-scale detection of Peach latent mosaic viroid (PLMVd) and Hop stunt viroid (HSVd). All 72 collected leaves (100%) from 2 PLMVd-and 2 HSVd-infected trees were positive in TIH, regardless of the geographic orientation of the scaffold, level of the canopy and position of the leaf in the shoot. In a large-scale survey in Serbia, we tested by TIH 871 trees of stone fruits, representing 602 cultivars from fruit collections in Belgrade, Čačak and Novi S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 26 publications
3
15
0
18
Order By: Relevance
“…However, HSVd was detected in three out of a total of 220 apricot trees, plus one accession of peach rootstocks, B-VA-2 (Table 2). Generally, the incidence of HSVd in the tested samples seemed to be low and consistent with results reported previously (Mandic et al 2008).…”
supporting
confidence: 92%
“…However, HSVd was detected in three out of a total of 220 apricot trees, plus one accession of peach rootstocks, B-VA-2 (Table 2). Generally, the incidence of HSVd in the tested samples seemed to be low and consistent with results reported previously (Mandic et al 2008).…”
supporting
confidence: 92%
“…Besides improving sensitivity, non-isotopic molecular hybridisation diagnostic methods have been concerned with reducing the processing time and the overall cost. In this way, in addition to the dot-blot, the tissue-printing technique has proved to be a simple and reliable method for sample preparation to detect plant viruses (Más and Pallas 1995;Cañizares et al 2001) and viroids (Romero-Durbán et al 1995;Mandic et al 2007).…”
mentioning
confidence: 99%
“…Afterwards, in a more comprehensive study, Mandić et al (2008) reported high PLMVd incidence (50%) in collection orchards. The viroid incidence in collections may be attributed to an initial introduction of contaminated plants.…”
Section: Discussionmentioning
confidence: 98%
“…In later studies, PLMVd was detected in more than half of the analyzed peach varieties from stone fruit collections (Mandić et al, 2008). PLMVd is a pathogen covered by special supervision of stone fruit mother blocks as regulated by the Ministry of Agriculture and Environmental Protection of the Republic of Serbia.…”
Section: Introductionmentioning
confidence: 98%